HUBUNGAN PENANGANAN SAMPAH RUMAH TANGGA DENGAN TIMBULAN SAMPAH DI RW 20 KELURAHAN CIPAGERAN KECAMATAN CIMAHI UTARA KOTA CIMAHI TAHUN 2023 - Bambang Purnama, Lubis; Rachmawaty, Dinar (Jurnal Sanitasi Profesional Indonesia, 2023)
Garbage is still an environmental problem that is considered serious in Indonesia, every day waste is generated from household activities with both organic and inorganic. This is because the amount of waste in Indonesia is so high that it is difficult for the government to determine the right way to solve the waste problem. The purpose of this study is to determine waste handling, facilities and infrastructure and waste generation. The type of research used is analytic with cross sectional design. The sampling method used purposive sampling and data were collected by observation, then data analysis was done using chi-square. The average amount of waste generation in RW 20 Cipageran Village, North Cimahi District, Cimahi City on May 4 - 11 was 0.36 kg/person/day at the sorting stage, the result was that 19% fulfilled the requirements, while 81% did not meet the requirements. the results of observations at the sorting stage showed that 40% fulfilled the requirements, while 60% did not meet the requirements, the results of observations at the sorting stage showed that 63% fulfilled the requirements, while 36% did not meet the requirements. <0.05) then Ha is accepted so that there is a significant relationship between waste sorting and waste generation, the result of the analysis is that the value of p = 0.003 (<0.05) then Ha is accepted so that it can be interpreted that there is a significant relationship between waste storage and waste generation, the results of the analysis that the value of p = 0.160 (> 0.05) then Ha is rejected so that it can be interpreted that there is no significant relationship between waste collection and waste generation in RW 20